ROLE OF MULTISYSTEM PHYSIOLOGICAL DYSREGULATION IN COGNITIVE IMPAIRMENT AND FRAILTY. (11th November 2018) - Gross, A; Chu, N; Carlson, M C; Xue, Q
Abstract: Although inflammation underlies both dementia and frailty, the role of dysregulation across multiple physiological systems in the genesis of these two syndromes is unclear. We used data from the Women's Health and Aging Study II (N=230) to derive, via factor analysis, a multisystem physiological dysregulation factor from 12 serum biomarkers of stress response and energy metabolism. We used multinomial logistic regression to predict onset of (1) dementia only, (2) frailty only, and (3) both over 9 years. Compared to women who never developed dementia or frailty, greater physiological dysregulation was associated with incidence of dementia (OR=1.42), frailty (OR=1.77), and both (OR=2.34). After adjustment for IL-6, physiological dysregulation was no longer associated with incidence of dementia (OR=1.01) but remained associated with onset of frailty (OR=1.46) and frailty/dementia (OR=1.74). These data suggest inflammation may be a common risk factor for dementia and frailty, but multisystem physiological dysregulation appears specific to frailty onset.